The Influence of Servant Leadership, Human Relations, Integrity, and Rewards on Employee Performance at Leksono Junior High School - Tyas, Dwi Ana Kusumaning; Wijayanti, Eka Septi; Seno, Gigih Aryo; Astuti, Margi (UM Purwokerto Press, 2025)
Employee performance is a crucial factor for organisations, including educational institutions. This study aims to determine the effect of servant leadership, human relations, integrity, and rewards on employee performance at Leksono Junior High School. Using a quantitative approach, this study involved 48 employees as a sample taken through the quota sampling technique. Data were collected using questionnaires and analysed by multiple regression using SPSS 27. The results showed that servant leadership, human relations, integrity, and reward had a positive and significant effect on employee performance, both partially and simultaneously. The reward variable has the greatest influence on employee performance. This study concludes that improving aspects of servant leadership, human relations, integrity, and reward can improve employee performance at Leksono Junior High School. In addition, this study also found that service-focused leadership can build harmonious working relationships, increase employee trust, and encourage them to work better. The integrity factor is also very important because employees who have high integrity can get rewards. For future research, it is recommended to explore other factors such as work motivation and organisational environment and expand the scope of research to other agencies in order to obtain more comprehensive results and broader generalisation.